Elevated lactate/albumin ratio is associated with poor prognosis in sepsis patients: a systematic review and meta-analysis: lactate/albumin ratio and sepsis - Zhao, Xian; Peng, Qin; Li, Weiwei; Hu, Dongmei; Guan, Yue; Wang, Jingwen (Journal of Medical Biochemistry, 2023)
Background: The aim of this study was to explore the association between lactate/albumin ratio and the prognosis of sepsis patients. Methods: A computerized search was performed in Pubmed, EMbase, Ovid, Medline, and Google Scholar to collate relevant studies. The results were compared using standardized mean differences (SMD)/odds ratio (OR) and 95% confidence intervals (CI). Prospective and retrospective cohort studies were both included in this study. Results: A total of nine studies involving 3039 participants were included. Pooled analysis revealed that survivors had substantially lower lactate/albumin ratio than non-survivors (SMD=-2.02, 95% CI: -2.76 to -1.28, I2=97.4%). Further, our results also indicated that elevated lactate/albumin ratio is an independent risk factor for mortality (OR=2.16, 95% CI: 1.58 to 2.95, I2=76.2%) and multiple organ dysfunction syndrome (MODS) (OR=3.41, 95% CI: 1.78 to 6.50, I2=0.0%) in septic patients. Moreover, according to the area under curve (AUC) results, the lactate/albumin ratio also presented good discriminatory power to predict mortality (AUC=0.75, 95% CI: 0.68 to 0.84, I2=92.9%) and MODS (AUC=0.78, 95% CI: 0.68 to 0.91, I2=65.1%) in septic patients. Begg’s and Egger’s test suggested no publication bias in the included studies. Conclusions: Our results highlighted that the lactate/albumin ratio is an important prognostic factor for MODS and mortality in sepsis patients, having good capabilities in identifying MODS and mortality.